2023
DOI: 10.1177/20552076231203599
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness, safety and patients’ perceptions of an immersive virtual reality–based exercise system for poststroke upper limb motor rehabilitation: A proof-of-concept and feasibility randomized controlled trial

Jiayin Chen,
Calvin Kalun Or,
Zhixian Li
et al.

Abstract: Objective This study aimed to examine the effectiveness, safety and patients’ perceptions of an immersive virtual reality (VR)–based exercise system for poststroke upper limb rehabilitation. Methods A proof-of-concept, 2-week randomized controlled trial was conducted. Fifty stroke patients were randomly assigned to either use the immersive VR-based exercise system to perform upper limb exercises for 2 weeks (intervention) or play commercial games (control). Effectiveness, safety and patients’ perceptions of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 75 publications
0
1
0
Order By: Relevance
“…Previous studies have demonstrated that an immersive VR-based exercise system is a potentially effective, safe, and acceptable approach toward supporting poststroke motor rehabilitation. 21 Furthermore, a systematic review and meta-analysis of randomized controlled trials confirmed the effectiveness of VR-supported exercise therapy for the rehabilitation of patients with suboptimal health. 22 Additionally, a study with both practicality and acceptability in Taiwan revealed that older adults have positive perceptions towards accepting and using VR to support active aging.…”
Section: Introductionmentioning
confidence: 89%
“…Previous studies have demonstrated that an immersive VR-based exercise system is a potentially effective, safe, and acceptable approach toward supporting poststroke motor rehabilitation. 21 Furthermore, a systematic review and meta-analysis of randomized controlled trials confirmed the effectiveness of VR-supported exercise therapy for the rehabilitation of patients with suboptimal health. 22 Additionally, a study with both practicality and acceptability in Taiwan revealed that older adults have positive perceptions towards accepting and using VR to support active aging.…”
Section: Introductionmentioning
confidence: 89%